Clinical Basis for Creating an Osseointegrated Neural Interface - Karczewski, Alison M.; Zeng, Weifeng; Stratchko, Lindsay M.; Bachus, Kent N.; Poore, Samuel O.; Dingle, Aaron M. (Frontiers in Neuroscience, 2022)
As technology continues to improve within the neuroprosthetic landscape, there has been a paradigm shift in the approach to amputation and surgical implementation. Although recent reconstructive surgical techniques such as targeted muscle reinnervation (TMR) or regenerative peripheral neural interfaces (RPNI) have improved motor control with bionic limbs, function remains limited by socket attachments and percutaneous wiring. Additionally, these interface designs do not sufficiently restore sensation, limiting their adoption for everyday use. In response to these challenges, the Osseointegrated Neural Interface (ONI) was developed as a solution designed to optimize range of motion and improve bidirectional signaling through restoration of sensation. Relying on the concepts of osseointegration and nerve regeneration, this interface can be used to power a prosthetic device capable of sophisticated control. The bone serves as an anchor for the endoprosthesis while the medullary canal offers a protective environment for the electrodes and interface hardware. This anatomic dissection study used three upper limb and three lower limb cadavers for identification and measurement of the major peripheral nerves. CT imaging was used for morphologic bone evaluation and virtual implantation data determined the amount of residual medullary space available for housing the ONI hardware. The results from this study help establish a preclinical modeling for the ONI that can serve as a guide for surgical implementation of an endoprosthesis with intramedullary electrodes.